Mental health and blame attribution of prisoners in Iceland - Ásta Lilja Bragadóttir 1977- (2016)
The object of the current study was to assess Icelandic prisoners´ mental health as well as the interrelationship between mental health and blame attribution. Seventy two percent of male prisoners population in Iceland participated in the study. The Beck Hopelessness Scale along with Bradburn´s Affect Balance Scale were used to assess mental health, and the Gudjonsson Blame Attribution Inventory was used to estimate blame attribution. Hopelessness was associated with external blame attribution and guilt feelings, and guilt feelings negatively correlated with affect balance. Older prisoners had longer sentences than younger ones, and those who had long sentences had more time left to serve than those who had short sentences. Prisoners did not differ in any way between prisons. Moreover, they did not differ in mental health or blame attribution, no matter what type of crime they had committed.